2010
DOI: 10.1183/09031936.00088410
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa accentuates epithelial-to-mesenchymal transition in the airway

Abstract: Epithelial-to-mesenchymal transition (EMT) has been implicated in the dysregulated epithelial wound repair that contributes to obliterative bronchiolitis (OB) after lung transplantation. Acquisition of Pseudomonas aeruginosa in the transplanted airway has been shown to be a risk factor for the development of OB. We investigated the potential of P. aeruginosa to drive EMT in primary bronchial epithelial cells (PBECs) isolated from lung transplant recipients.Changes in the expression of epithelial and mesenchyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…Recently TNFα has been shown to accentuate TGF-β1 driven EMT in a range of cell types highlighting a potential link between EMT and inflammation [17][18][19][20][21][22][23]. However, the mechanisms responsible have been ill-defined and further studies are required to elucidate the signalling pathways involved so potential therapeutic targets to limit or even reverse inflammatory driven EMT can be identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently TNFα has been shown to accentuate TGF-β1 driven EMT in a range of cell types highlighting a potential link between EMT and inflammation [17][18][19][20][21][22][23]. However, the mechanisms responsible have been ill-defined and further studies are required to elucidate the signalling pathways involved so potential therapeutic targets to limit or even reverse inflammatory driven EMT can be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas aeruginosa whole cell lysate was prepared from a laboratory reference strain (NCTC10662) as previously described [23,24]. Briefly, the strain was grown overnight on 1% horse blood agar plates, harvested into PBS and standardised to 0.2 at an optical density of 600 nm.…”
Section: Pseudomonas Aeruginosa Whole Cell Lysate Preparationmentioning
confidence: 99%
“…Bacterial infection with Pseudomonas aeruginosa has been shown to significantly increase inflammation in lung transplant recipients [167]. BORTHWICK et al [168] have shown that bacteria are able to induce EMT in the presence of TGF-b. This effect is indirect and due to the activation of immune cells [168].…”
Section: Emt and Bo Following Lung Transplantationmentioning
confidence: 99%
“…BORTHWICK et al [168] have shown that bacteria are able to induce EMT in the presence of TGF-b. This effect is indirect and due to the activation of immune cells [168]. It would be interesting to investigate whether infection with cytomegalovirus, which constitutes a risk factor for BO, can induce EMT.…”
Section: Emt and Bo Following Lung Transplantationmentioning
confidence: 99%
“…The recognition of microbial factors stimulates the cells to produce other PRRs, acute phase proteins and cytokines, to recognize the microbes more efficiently, inhibit bacterial growth, recruit inflammatory cells to the site of infection, and to enhance the phagocytic activity [24]. Alveolar epithelium expresses TGF-β1, which is upregulated further upon an infection with respiratory bacterial pathogens, including Mycobacterium tuberculosis (M. tuberculosis) [27][28][29], Pseudomonas aeruginosa [30][31][32][33], nontypeable Haemophilus influenzae (NTHi) [34][35][36], and pneumococcus [35,37].…”
Section: Epithelial Cellsmentioning
confidence: 99%